Dávkování základní farmakoterapie a jeho vliv na prognózu pacientů hospitalizovaných pro srdeční selhání - Krynský, Tomáš; Mayer, Otto; Bruthans, Jan; Bílková, Simona; Jirák, Josef (Vnitrni lekarstvi, 2023)
BACKGROUND: We analyzed the prescription and dosage of essential pharmacotherapy in chronic heart failure (HF) at the time of discharge from the hospitalization for cardiac decompensation and how it may have influenced the prognosis of the patients. METHODS: We followed 4097 patients [mean age 70.7, 60.2% males] hospitalized for HF between 2010 and 2020. The vital status we ascertained from the population registry, other circumstances from the hospital information system. RESULTS: The prescription of beta-blockers (BB) was 77.5% (or only 60.8% of BB with evidence in HF), 79% of renin-angiotensin system (RAS) blockers, and 45.3% of mineralocorticoid receptor antagonists (MRA). Almost 87% of patients were treated with furosemide at the time of discharge, while only ≈53% of patients with ischemic etiology of HF took a statin. The highest target dose of BB was recommended in ≈11% of patients, RAS blockers in ≈ 24%, and MRA in ≈ 12% of patients. In patients with concomitant renal insufficiency, the prescription of BB and MRA was generally less frequent and on a significantly lower dosage. In contrast, the opposite was true for the RAS blocker (however statistically insignificant). In patients with EF ≤ 40%, the prescription of BB and RAS blockers were more frequent but in a significantly lower dosage. On the contrary, MRAs were recommended in these patients more often and in higher doses. In terms of mortality risk, patients treated only with a reduced dose of RAS blockers showed a 77% higher risk of death within one year (or 42% within five years). A significant relationship was also found between mortality and the recommended dose of furosemide. CONCLUSIONS: The prescription and dosage of essential pharmacotherapy are far from optimal, and in the case of RAS blockers, this affected the patient's prognosis as well.
Keywords: lidé; furosemid; Prognosis; Mineralocorticoid Receptor Antagonists; prognóza; Heart Failure; Female; srdeční selhání; therapy; antagonisté mineralokortikoidních receptorů; Humans; tepový objem; Furosemide; Stroke Volume; beta blokátory; type 2 diabetes; mužské pohlaví; chronic heart failure; dose; ženské pohlaví; Adrenergic beta-Antagonists; cardiac decompensation; Male; Angiotensin Receptor Antagonists; mortality; antagonisté receptorů pro angiotenzin; dose of biotin